Work Emotion Intervention and Guidance Training Method for Enterprise Employees Based on Virtual Reality - Lixun Zhu (Hindawi-Wiley, 2022)
Objective. Improper management of employees' emotions has a great impact on work status and work efficiency, and emotional management has increasingly become a very important part of corporate human resource management. How to adjust the various emotions of employees, so that employees can work in a fuller and more passionate attitude, is a problem that enterprise managers need to consider. From the perspective of employees themselves, a good mood will also bring happiness and satisfaction to life and work. Only in this way can the company and the employees be satisfied with each other and continue to maintain the good development momentum of the company. Method. This paper proposes a new method of using virtual reality scenes to induce human emotions. Based on computer science and psychological cognitive science, a scene library of "virtual reality emotion induction system" is constructed. Emotion induction based on virtual reality scenes has better interactivity and generalization, as well as stronger immersion and user operability. Its emotional arousal is high, the data is reliable, and the interference of environmental factors in the induction process is weakened, and relatively objective emotional data can be obtained. The factors affecting the emotional management of the enterprise are investigated by means of a questionnaire survey, statistics and problems are found, and the objective problems existing in the emotional management work of the company are determined. According to the analysis, the problems are summarized, and it is believed that the company still has certain room for improvement and improvement potential in terms of corporate culture construction, emotional counseling system construction, and human resource career planning. In the research of this paper, through the combination of theory and practice, the enterprise's emotional management work has been comprehensively analyzed, and the practical problems existing in its emotional management work have been found through questionnaires. Results/Discussion. In the field of enterprise human resource management, emotion management is always an eternal topic worthy of our attention. But unfortunately, emotional management has not been given enough attention by managers. Most companies often think that emotions are their own business. Employees should self-regulate, control, and tolerate themselves. They should not bring personal emotions to work and even think that emotional work is unprofessional. This kind of misunderstanding has led to the fact that emotional management has not received due attention and affirmation in many enterprises.